SALT LAKES OF THE WEST KAZAKHSTAN REGION AS OBJECTS OF MEDICAL TOURISM - Kazhmurat M. AKHMEDENOV; Rysty A. KHALELOVA (Geo Journal of Tourism and Geosites, 2021)
West Kazakhstan region is also rich in unique balneological hydromineral resources. The aim of the study was to review the studied, as well as little-known and promising, salt lakes of West Kazakhstan region, which have hydromineral resources suitable for balneological and recreational use is given. As a result of the field and laboratory researches in 2017-2020, 7 promising balneological sites were studied – the Lakes Bolshoy Sor, the Alzhansor, the Sorkol, the Hakisor, the Aralsor, the Edilbaysor, the Koysarysor. It was established that the studied peloids correspond to the genetic type of mainland silt mineral (sulphide) therapeutic mud typical of arid regions. According to the main indicators, the studied peloids are generally suitable for use in recreational, therapeutic and medical purposes, and in terms of the content of salts and therapeutically valuable components, they are not inferior to the medical mud of the resorts of Western Kazakhstan and the Dead Sea recognized in balneological practice.